Economic calculus qua an instrument to support sustainable development under increasing risk - Grzegorz Drozdowski (Journal of Risk and Financial Management, 2021)
Investment decisions in the field of sustainable development should be taken based on an economic calculation, taking into account the analysis of a diverse economic environment. The economic calculus of an enterprise is treated as a kind of way of thinking about the rationality of decisions made by an entrepreneur. In the case of sustainable development, the economic calculus serves as an instrument to support the selection of the investment measure. The result of the economic calculus is based on various types of economic parameters, which are subject to frequent changes and high risk. A risk-based financial account may be of little use in the context of the unpredictability of the forecasted situations. In the article, I attempted to determine the importance of a variable interest rate in the economic calculus of a company as an instrument to support sustainable development. For this purpose, I modified the Net Present Value (NPV) meter, which contains actual (variable) discount rates.
Keywords: 330; economic calculus; sustainability; variable discount rate; economic calculus of sustainability; financial management; risk; uncertainty